2004
DOI: 10.1111/j.1741-6892.2004.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal red blood cell transfusions

Abstract: Red blood cell and blood product transfusions in the fetus, neonate and premature infant are often administered with poorly defined indications and unintentional adverse consequences. Products may be altered in an effort to limit potential adverse events or be specially selected to meet the unique needs of a specific diagnosis. One area of particular concern to neonatologists is selecting blood for small volume (5-20 ml/kg) transfusions in prematures.For infants, red blood cells (RBC's) collected in anticoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…It has been proposed that anaemia causes reduced mesenteric blood flow leading to intestinal hypoxia and subsequent mucosal injury [8, 36-39]. There is evidence to suggest that this transient hypoxia followed by re-oxygenation (e.g., after RBCT to treat anaemia) is a component of the pathogenesis of diseases involving a change in blood flow to the bowel, including NEC, through reperfusion injury [11, 18, 22-24, 40]. The association between Hb, tissue perfusion, and oxygen delivery is not clear [39]; the critical Hb level at which the risk from anaemia outweighs the risk of NEC from RBCT has not been identified [64, 71].…”
Section: Anaemia Blood Transfusion and Necmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that anaemia causes reduced mesenteric blood flow leading to intestinal hypoxia and subsequent mucosal injury [8, 36-39]. There is evidence to suggest that this transient hypoxia followed by re-oxygenation (e.g., after RBCT to treat anaemia) is a component of the pathogenesis of diseases involving a change in blood flow to the bowel, including NEC, through reperfusion injury [11, 18, 22-24, 40]. The association between Hb, tissue perfusion, and oxygen delivery is not clear [39]; the critical Hb level at which the risk from anaemia outweighs the risk of NEC from RBCT has not been identified [64, 71].…”
Section: Anaemia Blood Transfusion and Necmentioning
confidence: 99%
“…The RBCT guidelines used in the Neonatal Unit (NNU) are subjective and generalized [17, 18]. Anaemia impacts the clinical status when the oxygen-carrying capacity drops below an adequate threshold to meet the demands of oxygen consumption.…”
Section: Current Guidelinesmentioning
confidence: 99%
“…Several theoretical and practical studies have demonstrated that using RBC stored up to 42 days is safe. It has been proven that possible changes in biochemical or toxic factors are of no clinical significance provided that transfusion volumes are small [5][6][7]. Thus, this rationale does not apply to large-volume transfusions, such as exchange transfusion or transfusion in extensive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the knowledge gained from research and practice in prescribing RBC transfusion, there are still controversies and a lack of unique indications in neonatal transfusion therapy [1,7,15]. In our ward, RBC transfusion guidelines allow for some physician discretion on site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation